EVALUATION OF CEMENT BOND USING CEMENT BOND LOG (CBL) AND VARIABLE DENSITY LOG (VDL) DATA: CASE STUDY OF WELL-X IN A 9-5/8 IN PRODUCTION ZONE - Poen, Harley
Indonesia employs the Carbon Capture and Storage/Carbon Capture Storage and Utilization (CCS/CCUS) technique to mitigate carbon emissions mainly from the energy sector. CCS/CCUS is an effective method for mitigating global warming by minimizing the release of CO2 into the atmosphere. The well-X is designed for injecting CO2 into the Ngrayong formation, which consists of sandstone lithology, at a depth ranging from 854 to 862 meters, for the purpose of storage. Prior to proceeding, it is necessary to assess and remedy the well-X in order to comply with current technical standards, ensuring a successful completion of the operation's objectives. This study aims to assess the quality of bonds between cements by interpreting Cement Bond Log (CBL) dan Variable Density Log (VDL) data and calculating bonding index in well-X within the 9 5/8 inch zone. This cement evaluation was conducted to mitigate the probable leakage of CO2 to the surface. The approach proposed involves analyzing the CBL and VDL data both vertically and horizontally, followed by computing the amplitude interpretation outcomes to ascertain the bonding index at each interval of well-X. After conducting bonding index calculations and analyzing CBL and VDL data, it was determined that the cement in the 9-5/8 inch zone needed to be re-cemented at multiple locations due to the findings falling below the current technical criteria. Failure to address this issue may result in the CO2 that has been injected flowing through the poor cement bond, possibly causing to surface leaks.